Experimental Study on Dual-PCM Gradient Thermal Management for Lithium-Ion Batteries with Wide Temperature Adaptability - Wang Tieying; Liu Songsong; Su Yuanxiang; Liu Shengchun; Shi Qianlei; Xu Chao; Liao Zixuan (Zhileng xuebao)
In this study, a new method for passive thermal management of lithium-ion batteries based on paraffin/expanded graphite/bamboo charcoal composite bilayer phase change materials is proposed. In order to solve the problem of limited temperature control range of existing phase change materials, a dual phase change temperature (30°C/50°C) gradient structure is constructed, and a composite phase change system with dual phase change temperature regulation is developed by combining the high thermal conductivity of expanded graphite with the porous adsorption properties of bamboo charcoal. The experimental results show that at 40°C ambient temperature and 5C large multiplication rate working condition, the temperature rise of the battery with the double-layer phase change material is 37.8% lower than that of the non-phase change material group (43.3°C vs. 69.6°C); at low temperatures (-10°C and 0°C), the double-layer phase change material broadens the range of the battery's effective working temperature through the synergistic effect of latent heat release of the phase change and the heat storage in the pores. The composite phase change system realizes intelligent thermal management across a broad temperature spectrum (-10°C~40°C) through the dual-phase change mechanism, providing an innovative solution for thermal safety regulation of batteries, which has significant engineering application value.